Dampak Perusahaan Kelapa Sawit terhadap Pendapatan dan Kesejahteraan Masyarakat Sekitar di Kecamatan Pulau Laut Tengah Kabupaten Kotabaru - Yahya Setiawan; M Rusmin Nuryadin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
This study aims to (1) To find out the income of the people who live around the oil palm company in Pulau Laut Tengah District, Kotabaru Regency, (2) to find out the welfare of the community living around the palm oil company in Pulau Laut Tengah District, Kotabaru Regency. Respondents in this study were 94 heads of households from Pulau Laut Tengah District, Kotabaru Regency with data collection techniques through questionnaires, observations and documentation. The data analysis technique used is descriptive and quantitative analysisThe results of this study indicate that the income of respondents working in oil palm companies has a salary of 2 million to 5 million rupiah depending on the status of work. Respondents related to oil palm companies and those not related to oil palm companies in the villages of Mekarpura, Salino and Sungai Pasir are quite well off and able to meet their daily needs